Development Magnetic Science Park Props Based On Science Literacy To Improve Understanding Concept Of Magnetic Force In Grade IV Elementary School - Sianturi, Magdalena Ernesta (Phenomenon : Jurnal Pendidikan MIPA, 2023)
Teaching aids are tools that help teachers convey abstract material to be more concrete in classroom learning. The props in the development research aim to form science literacy skills to make it easier for grade IV elementary school students to understand the concept of magnetic force. This research is based on the level of understanding of students' concepts related to magnetic force which is still low, due to the lack of variation in the use of media/tools in science learning in the classroom and the lack of student learning motivation. This research is a development research (D&D) with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) which aims to produce valid and effective science literacy-based teaching aids. The research subjects were fourth grade students at SDN Bandung city. Data were obtained from observations, interviews, questionnaires, expert validation to see the validity of the teaching aids, and test results to see the effectiveness of the teaching aids. The results showed that the average value of the validity of teaching aids by material experts was 96.8% and media experts amounted to 97.9%, while by learning experts amounted to 97.5%. Based on the results of the pretest and posttest, it shows an increase in understanding of the concept of magnetic force after using science literacy-based teaching aids with an average score from 26 to 78 which can be said to be quite effective.